2011
DOI: 10.1038/nrc3069
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of second malignancies after modern radiotherapy

Abstract: Recent advances in radiotherapy have enabled the use of different types of particles, such as protons and heavy ions, as well as refinements to the treatment of tumours with standard sources (photons). However, the risk of second cancers arising in long-term survivors continues to be a problem. The long-term risks from treatments such as particle therapy have not yet been determined and are unlikely to become apparent for many years. Therefore, there is a need to develop risk assessments based on our current k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
271
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(275 citation statements)
references
References 98 publications
(114 reference statements)
2
271
1
1
Order By: Relevance
“…In addition, according to Dorr and Herrmann, 31 , 32 the majority of second cancers are induced within the penumbra of radiotherapy. Moreover, some papers reported that second cancers occurred in the low‐dose region, especially in pediatric patients 33 , 34 , 35 . Thus, the low dose should be delivered accurately and evaluated strictly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Dorr and Herrmann, 31 , 32 the majority of second cancers are induced within the penumbra of radiotherapy. Moreover, some papers reported that second cancers occurred in the low‐dose region, especially in pediatric patients 33 , 34 , 35 . Thus, the low dose should be delivered accurately and evaluated strictly.…”
Section: Discussionmentioning
confidence: 99%
“…Scanned particle therapy can produce sharp dose gradients with a finite range of the beam and can thus provide higher normal tissue sparing. This reduces both side effects as well as the risk of secondary cancer [Newhauser and Durante, 2011]. Treatment of lung tumors with particles is still challenging due to interplay and radiological path length changes [Bert and Durante, 2011].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The role of RIBEs on secondary cancer risk has been considered for some time in relation to low dose environmental exposures and out-of-field regions in radiotherapy (63,64). Attempts to attribute additional cancer risk to these effects have remained challenging as current empirical models of secondary cancer risk do not address specific mechanisms such as in vivo signalling effects.…”
Section: Implications For Radiotherapy and Cancer Riskmentioning
confidence: 99%